The Development of Medieval Archaeology in Armenia and the “Vayots Dzor Silk Road Survey” (VDSRS) - Babajanyan, Astghik; Franklin, Kate (History and Culture, 2025)
This article addresses the current challenges facing medieval archaeology and outlines the necessary steps to align it with global trends, ensuring its sustainable development. Key challenges include the need for methodological innovation and enhanced interdisciplinary collaboration, both of which are essential for a more comprehensive study of Armenia’s medieval past. The article emphasizes the importance of a comprehensive, interdisciplinary approach to archaeological research that goes beyond merely presenting excavated sites and artifacts. By synthesizing the results of excavated monuments and examining them in the context of the surrounding landscape, this approach facilitates the reconstruction of a complete and nuanced picture of medieval life. In light of the issues and challenges identified for advancing medieval archaeology in Armenia, the VDSRS project prioritizes these objectives in its research agenda. The project’s landscape approach integrates the study of archaeological sites, architectural monuments, historical and epigraphic sources, and material culture to gain insights into how people historically shaped and interacted with their environment. Building on Armenia’s rich tradition of medieval archaeology and incorporating new research findings, VDSRS aims to elevate Armenian archaeology within international academic discourse, fostering cross-cultural dialogue and situating Armenia within both regional and global medieval contexts. Through this approach, the project enhances our understanding of the significance of Armenia’s medieval heritage within the broader framework of the region’s history.